The Goal-Oriented Model Evaluation of Implementing Teaching Factory in Refrigeration and Air Conditioning at SMK Center Of Excellence, DK Jakarta - Husna, Aghnina Camilla; Muksin, Muksin; Soeprijanto, Soeprijanto (Journal of Educational Sciences, 2025)
Teaching factory is a real production-based learning method, such as making, selling products, or providing services in an educational environment. This study aims to assess the level of implementation of the Teaching Factory learning program on the expertise competency of Refrigeration and Air Conditioning Engineering (TPTU) at the Center of Excellence Vocational High School of the Special Region of Jakarta based on the objectives of the program itself (Goal Oriented). The approach used in this study is a mixed method with data collection techniques through interviews, observations, documentation, and questionnaires. This study was conducted at the Centre of Excellence Vocational School which organizes a learning Teaching Factory on the competence of refrigeration and air conditioning engineering expertise in the Special Region of Jakarta. The sample of this study consisted of 5 schools with an average evaluation result of 80,58%. Based on this value, it can be concluded that the implementation of the Teaching Factory on the competence of refrigeration and air conditioning engineering expertise at the SMK Pusat Keunggulan DK Jakarta was carried out well.